Answer:
D
Step-by-step explanation: just trust me
Answer:
hope you liked it!
Step-by-step explanation:
give a thanks if it is correct!
2(x - 2) + 3(x + 1) = 9
2x - 4 + 3x + 3 = 9 <em>distributed the 2 and 3 on the left side</em>
5x - 1 = 9 <em>added like terms (2x + 3x) and (-4 + 3)</em>
5x = 10 <em>added 1 to both sides</em>
x = 2 <em>divided 5 from both sides</em>
Answer: x = 2
Answer:
(gxf)(1) = - 12
Step-by-step explanation:
Let f(x) = -4x + 7 and g(x) = 2x - 6.
(gxf)(1) = g(1)xf(1)
but : f(1) = -4(1)+7 =7-4 = 3 and g(1)=2(1)-6 =2-6 = -4
so : (gxf)(1) = g(1)xf(1) = (-4)(3)=-12